Therapeutic drug monitoring of naltrexone and 6β-naltrexol during anti-craving treatment in alcohol dependence: reference ranges - Brünen, Sonja; Bekier, Nina Kim; Hiemke, Christoph; Korf, Felix; Wiedemann, Klaus; Jahn, Holger; Kiefer, Falk (Alcohol and alcoholism, 2019)
This article shows the use of therapeutic drug monitoring in alcohol dependent patients, who are treated with naltrexone. The plasma concentrations of naltrexon
Advance access publication date: 27 September 2018
Gesehen am 26.06.2019